Automatic Detection of Flavescence Dorée Symptoms Across White Grapevine Varieties Using Deep Learning - Boulent, Justine; St-Charles, Pierre-Luc; Foucher, Samuel; Théau, Jérome (Frontiers in Artificial Intelligence, 2020)
Flavescence dorée (FD) is a grapevine disease caused by phytoplasmas and transmitted by leafhoppers that has been spreading in European vineyards despite significant efforts to control it. In this study, we aim to develop a model for the automatic detection of FD-like symptoms (which encompass other grapevine yellows symptoms)